Graphene Nanoplatelets Impact on Concrete in Improving Freeze-Thaw Resistance - Guofang Chen; Mingqian Yang; Longjun Xu; Yingzi Zhang; Yanze Wang (Applied Sciences, 2019)
Graphene nanoplatelets (GNP) is a newly nanomaterial with extraordinary properties. This paper investigated the effect of GNP on the addition on freeze−thaw (F−T) resistance of concrete. In this experimental study, water to cement ratio remained unchanged, a control mixture without GNP materials and the addition of GNP was ranging from 0.02% to 0.4% by weight of ordinary Portland cement was prepared. Specimens were carried out by the rapid freeze-thaw test, according to the current Chinese standard. The workability, compressive strength, visual deterioration and mass loss of concrete samples were evaluated. Scanning electron microscopy also applied in order to investigate the micromorphology inside of the concrete. The results showed that GNP concrete has a finer pore structure than ordinary concrete; moreover, the workability of GNP concrete reduced, and the compressive strength of specimens was enhanced within the appropriate range of GNP addition; in addition, GNP concrete performed better than the control concrete in the durability of concrete exposed to F-T actions. Specimens with 0.05% GNP exhibited the highest compressive property after 200 F−T cycles compared with other samples.